[tex]\displaystyle\bf\\\Big(x-3\Big)^{3} +27=\Big(x-3\Big)^{3} +3^{3} =\\\\\\=\Big(x-3+3\Big)\cdot\Big[(x-3)^{2} -(x-3)\cdot 3+3^{2} \Big]=\\\\\\=x\cdot\Big(x^{2} -6x+9-3x+9+9\Big)=\\\\\\=x\cdot\Big(x^{2} -9x+27\Big)[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle\bf\\\Big(x-3\Big)^{3} +27=\Big(x-3\Big)^{3} +3^{3} =\\\\\\=\Big(x-3+3\Big)\cdot\Big[(x-3)^{2} -(x-3)\cdot 3+3^{2} \Big]=\\\\\\=x\cdot\Big(x^{2} -6x+9-3x+9+9\Big)=\\\\\\=x\cdot\Big(x^{2} -9x+27\Big)[/tex]